Improving land governance for more equitable fish farm development in Myanmar - Belton, Ben (Michigan State University, 2017)
This note seeks to contribute to the ongoing debates around the revision of Myanmar’s 2012 Farmland Law. It summarizes key findings of research conducted in the main fish farming areas of Myanmar on the relationship between aquaculture (fish farming) and land use. It makes recommendations for the revision of land use regulations that would allow aquaculture to develop in a manner that benefits small producers and yields more equitable outcomes.